Students’ Academic Dishonesty In Midwifery Department - Rani Autila (RAM PUBLISHER, 2026)
This research was conducted to describe students’ academic dishonesty in examination process at Midwifery Department of Sekolah Tinggi Ilmu Kesehatan Indonesia. This study used the theory from Miller et al (2017) students’ academic dishonesty is a fraudulent or unfair act to produce better results on exams, papers, assignments, and other learning assignments. The researcher used a qualitative approach with descriptive research. Techniques in data collection is questionnaires. Research result show that the forms of academic dishonesty that students sometimes do are copy friends’ answer during exam, allow friends to copy answer sheet during the test, collaborate with friends during the test, use handphone to find answer during exam, use signal/finger code to friend to get answer. The result of students’ academic dishonesty is sometimes 15 %.